Frank–Kasper Phases Identified in PDMS‐b‐PTFEA Copolymers with High Conformational Asymmetry. Issue 19 (10th July 2019) - Jeon, Seungbae; Jun, Taesuk; Jo, Seongjun; Ahn, Hyungju; Lee, Seungwoo; Lee, Byeongdu; Ryu, Du Yeol
Abstract: In the search for the formation of Frank–Kasper phases from diblock copolymer self‐assembly, a series of compositionally asymmetric poly(dimethylsiloxane)‐ b ‐poly(2, 2, 2‐triflouroethyl acrylate)s (PDMS‐ b ‐PTFEAs) are synthesized to produce PDMS‐rich phases with PDMS volume fractions ( f PDMS ) ranging from 0.746 to 0.869. As determined by small‐angle X‐ray scattering analysis, the Frank–Kasper σ and C14 phases are identified at f PDMS = 0.796 and 0.851, respectively, plausibly due to high conformational asymmetry (ε ≈ 2.20) between the two blocks. Intriguingly, the σ phase develops during heating from a short‐range liquid‐like packing (LLP) state, whereas the C14 phase is achieved at room temperature, which are both followed by a disordering at higher temperatures. Based on thermal experiments from a super cooled disordered state, the findings further provide compelling evidence of an LLP‐hexagonally packed cylinder‐σ transition and a direct pathway to the C14 phase during heating from an LLP state. Abstract : A series of compositionally asymmetric poly(dimethylsiloxane)‐ b ‐poly(2, 2, 2‐triflouroethyl acrylate)s (PDMS‐ b ‐PTFEAs) is synthesized to produce PDMS‐rich phases with PDMS volume fractions ( f PDMS ) ranging from 0.746 to 0.869. Owing to high conformational asymmetry (ε ≈ 2.20) between the two blocks, the Frank–Kasper σ and C14 phases are identified at f PDMS = 0.80 and 0.85, respectively.